Hubungan Persepsi Tentang Jerawat dengan Kepercayaan Diri Remaja di SMAN 16 Jakarta - Annisyah Annisyah; Refirman DJ Refirman DJ; Sri Rahayu (Biota, 2017)
Acne can appear to everyone when someone is entering adolescence. Every teenager will perceive acne individually. Acne problems can cause a person to become less confidence. Every teenager should be able to accept self-condition and maintaining skin care. Furthermore, they should make appearance as problem in self confidence. This study aims to determine the correlation between acne perception with teens’ self confidence in SMAN 16 Jakarta. The method used are descriptive method with survey techniques through correlational studies. The population of this research was grade X MIA. The sample used in this study were 106 students and taken by simple random sampling. The prerequisite test results indicated that the distributed data were normal and distributed homogeneous. Regression test was obtained by regression model Ŷ = 15.069 + 0,771X and shown by a linear relationship. Based on hypothesis test, correlation coefficient value of 0.791 indicates a relationship of strong category coefficient of determination indicated 62.6% perception contributed to the teens self confidence. This study shown that there was a positive relationship between the perception of adolescent acne with confidence in SMAN 16 Jakarta.